2020
DOI: 10.21203/rs.3.rs-26413/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association Between Obstructive Sleep Apnea-Hypopnea Syndrome and Outcomes in Patients with Myocardial Infarction in the Absence of Obstructive Coronary Artery Disease

Abstract: Background: Myocardial infarction in the absence of obstructive coronary artery disease (MINOCA) occurs in 5% to 10% of all patients with acute myocardial infarction. Obstructive sleep apnea-hypopnea syndrome (OSAHS) is linked to increased cardiovascular morbidity and mortality, but the relationship of OSAHS and outcomes in patients with MINOCA remains unknown. Objectives: We aimed to evaluate the association between OSAHS and clinical outcomes in patients with MINOCA.Methods and Results: Between January 2015 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Six studies reported an increased Hazard ratio (HR) of all-cause mortality with SDB compared with controls in patients with myocardial ischemia, 13,17,26,29,30,31 with the pooled HR of 1.39(95% CI 1.12-1.73, p=0.0027) (Fig 3). There was no obvious statistical heterogeneity (Cochran Q = 7.27, p =0.2; I 2 = 31%), and no evidence of bias (Egger intercept = 0.8883, p = 0.2548).…”
Section: All-cause Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies reported an increased Hazard ratio (HR) of all-cause mortality with SDB compared with controls in patients with myocardial ischemia, 13,17,26,29,30,31 with the pooled HR of 1.39(95% CI 1.12-1.73, p=0.0027) (Fig 3). There was no obvious statistical heterogeneity (Cochran Q = 7.27, p =0.2; I 2 = 31%), and no evidence of bias (Egger intercept = 0.8883, p = 0.2548).…”
Section: All-cause Mortalitymentioning
confidence: 99%
“…Sixteen studies reported an increased Hazard ratio (HR) of MACCEs outcomes with SDB compared with controls in patients with myocardial ischemia, 12,13,16,18,19,20,21,22,23,24,25,26,27,28,29,30 with the combined HR of 1.66(95% CI 1.41-1.94, P< 0.0001) (Fig 2). Some evidence of statistical heterogeneity (Cochran Q = 23.00, p=0.08; I 2 = 35%) was found by pooled effect size, which might be in part attributable to 1 randomized controlled trial.…”
Section: Major Adverse Cardiovascular or Cerebrovascular Events (Macces)mentioning
confidence: 99%
“…Thanks to the Jiaxing Institute of Arteriosclerotic Diseases. This manuscript has been released as a pre-print at (38).…”
Section: Data Availability Statementmentioning
confidence: 99%